2022
DOI: 10.1097/iop.0000000000002176
|View full text |Cite
|
Sign up to set email alerts
|

Acute Onset Endophthalmitis Following Bilateral Upper and Lower Eyelid Blepharoplasty

Abstract: A 59-year-old woman presented with iritis and uveitis in the OD approximately 3 weeks after she underwent a bilateral upper and lower blepharoplasty by an outside oculoplastic specialist. Examination revealed a visual acuity of hand motion in the OD, scleral ulceration suspicious for prior globe perforation, dense vitritis, and loculations and membranes on echography. The patient was diagnosed with acute onset exogenous endophthalmitis. Vitreous aspiration and intravitreal injection of vancomycin and ceftazidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Three patients developed endophthalmitis, all associated with full-thickness scleral perforations. 3,10,12 Of the 12 patients requiring closure of the wound, 9 (75%) received surgical intervention and 3 (25%) received topical tissue adhesive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three patients developed endophthalmitis, all associated with full-thickness scleral perforations. 3,10,12 Of the 12 patients requiring closure of the wound, 9 (75%) received surgical intervention and 3 (25%) received topical tissue adhesive.…”
Section: Resultsmentioning
confidence: 99%
“…After careful review of all resultant published articles (483), we identified 13 previously reported cases of corneal and scleral penetrating and perforating injuries after blepharoplasty (Table 2). 3,[6][7][8][9][10][12][13][14][15][16] In order to provide a more robust understanding of globe injuries from blepharoplasties, the 3 new cases reported above were integrated with the 13 previously reported in the literature.…”
Section: Literature Review and Analysismentioning
confidence: 99%